Pemberdayaan Ekonomi Melalui Wirausaha Ibu-Ibu PKK di Desa Bobotsari Kecamatan Bobotsari Kabupaten Purbalingga - Pipin Sri Sudewi; Amin Budiastuti; Susanti Budiastuti; Guntoro Guntoro; Sri Hartati (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2024)
Entrepreneurship is the process of creating, developing, and managing a new business, often starting from an idea or concept and evolving into a sustainable business. An entrepreneur is an individual who establishes, manages, and grows a business or venture with the aim of creating added value, generating profit, and managing risk. Engaging in entrepreneurship in a village offers many unique opportunities, particularly because of the distinct advantages and challenges compared to an urban environment. The village of Bobotsari in Purbalingga Regency, Central Java, has various potentials that can be developed to bussiness ventures to enhance the well-being of the community and the village economy